Development of an Internal Positive Control for Rapid Diagnosis of Avian Influenza Virus Infections by Real-Time Reverse Transcription-PCR with Lyophilized Reagents - Das, Amaresh (American Society for Microbiology, 2006)
We developed an internal positive control (IPC) RNA to help ensure the accuracy of the detection of avian influenza virus (AIV) RNA by reverse transcription (RT)-PCR and real-time RT-PCR (RRT-PCR). The IPC was designed to have the same binding sites for the forward and reverse primers of the AIV matrix gene as the target amplicon, but it had a unique internal sequence used for the probe site. The amplification of the viral RNA and the IPC by RRT-PCR were monitored with two different fluorescent probes in a multiplex format, one specific for the AIV matrix gene and the other for the IPC. The RRT-PCR test was further simplified with the use of lyophilized bead reagents for the detection of AIV RNA. The RRT-PCR with the bead reagents was more sensitive than the conventional wet reagents for the detection of AIV RNA. The IPC-based RRT-PCR detected inhibitors in blood, kidney, lungs, spleen, intestine, and cloacal swabs, but not allantoic fluid, serum, or tracheal swabs The accuracy of RRT-PCR test results with the lyophilized beads was tested on cloacal and tracheal swabs from experimental birds inoculated with AIV and compared with virus isolation (VI) on embryonating chicken eggs. There was 97 to 100% agreement of the RRT-PCR test results with VI for tracheal swabs and 81% agreement with VI for cloacal swabs, indicating a high level of accuracy of the RRT-PCR assay. The same IPC in the form of armored RNA was also used to monitor the extraction of viral RNA and subsequent detection by RRT-PCR.